Polymorphisms in M2+AlF5(H2O)7 (M2+ = Fe2+, Co2+, or Ni2+): Syntheses, Crystal Structures, and Characterization of New Mixed Metal Fluoride Hydrates - Jun Min Seo; Hongil Jo; Myung Ho Choi; Kang Min Ok; Hong Young Chang; Sun Woo Kim (Crystals, 2024)
Three new mixed metal fluoride hydrates, M2+AlF5(H2O)7 (M2+ = Fe2+, Co2+, or Ni2+), were synthesized and characterized. The crystals of M2+AlF5(H2O)7 were obtained using a hydrothermal method with a CF3COOH aqueous solution. The crystal structures displayed polymorphisms in C2/m (No. 12) or P-1 (No. 2) space groups, depending on temperature variations. The observed polymorphisms in M2+AlF5(H2O)7 are associated with changes in the bonding environment of [M(H2O)6]2+ and [AlF5(H2O)]2− octahedra, along with changes in hydrogen bonds and unit cell volumes. Infrared spectra and thermogravimetric analyses confirmed the presence of water molecules. The ultraviolet–visible spectra of M2+AlF5(H2O)7 revealed distinctive absorption bands dependent on the [M(H2O)6]2+ complex. This work provides a detailed account of the synthetic procedure, crystal structures, and spectroscopic characterization of M2+AlF5(H2O)7.